2007
DOI: 10.1007/s10350-007-0296-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Sequelae Affecting the Continence Organ: Incidence, Pathogenesis, and Treatment

Abstract: Surgical treatment should be the absolute exception. If the creation of a stoma is being considered, a resective procedure offering freedom from symptoms seems to be the more advantageous option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 54 publications
0
9
0
3
Order By: Relevance
“…Other aspects associated with incontinence include further disorders such as proctitis, colitis, and other disturbances involving the lower digestive tract. The therapeutic options mainly comprise management of associated aspects, such as proctitis or diarrhea; surgical intervention should be the absolute exception [60] . It has been reported that sucralfate treatment has a protective effect against experimental radiation colitis.…”
Section: Chronic Radiation Colitis (Table 2)mentioning
confidence: 99%
“…Other aspects associated with incontinence include further disorders such as proctitis, colitis, and other disturbances involving the lower digestive tract. The therapeutic options mainly comprise management of associated aspects, such as proctitis or diarrhea; surgical intervention should be the absolute exception [60] . It has been reported that sucralfate treatment has a protective effect against experimental radiation colitis.…”
Section: Chronic Radiation Colitis (Table 2)mentioning
confidence: 99%
“…Fecal Incontinence In contrast to rectal bleeding, the exact pathophysiology of radiation-induced fecal incontinence is not clearly understood by now. Due to the fact that in several patients with clinical measurable incontinence, no relevant morphologic changes of the anal sphincter complex -regarding thickness, etc,-were detected (Petersen et al 2007;Yeoh et al 1998). A group of other factors is hypothesized to build clinical correlates of incontinence.…”
Section: Pathophysiological Changesmentioning
confidence: 97%
“…A group of other factors is hypothesized to build clinical correlates of incontinence. Besides the core factor of a reduced sphincter tone, several clinical signs are considered to be associated with radiationinduced incontinence, like a reduced rectal compliance and squeeze pressure (Berndtsson et al 2002;Petersen et al 2007;Yeoh et al 1998). In this context, connective tissue remodeling of the rectum, including smooth muscle cell hypertrophy as well as decreased neural function due to damages in the myenteric plexus controlling the continencerelated muscles, seems to be very important regarding the development of fecal incontinence after radiotherapy.…”
Section: Pathophysiological Changesmentioning
confidence: 98%
“…Incontinence can affect up to 70% at 6 weeks, though some of these cases are due to acute colitis. A reasonable estimate is that about a third of patients suffer from fecal incontinence in the long term [7].…”
Section: Radiation Colitis Epidemiologymentioning
confidence: 99%